Aktivitas Anti Jerawat Ekstrak Etanol Biji Jamblang (Syzygium cumini L. Skeels) dalam Sediaan Emulgel - Misrahanum Misrahanum; Rena Novita Rezeki; Hilda Maysarah (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Jamblang (Syzygium cumini L. Skeels) contains antibacterial compounds and can be formulated into an emulgel form. This study aimed to determine the optimal concentration of ethanolic extract from jamblang seeds, develop emulgel formulations, and evaluate their antibacterial activity against Staphylococcus aureus and Staphylococcus epidermidis. The extraction was performed using 96% ethanol through maceration, followed by phytochemical screening and antibacterial testing using the well diffusion method. Phytochemical screening indicated the presence of alkaloids, flavonoids, saponins, tannins, and triterpenoids. Antibacterial testing of jamblang seed extract against S. aureus and S. epidermidis at various concentrations demonstrated significant inhibition. The emulgel formulations were prepared using jamblang seed extract at concentrations of 5%, 10%, and 15%, with 3% HPMC as the gelling agent. The emulgel exhibited strong antibacterial activity, with the largest inhibition zones observed in the 15% formulation (F3), measuring 21.44 ± 0.21 mm against S. aureus and 19.02 ± 0.60 mm against S. epidermidis. Stability tests showed that the organoleptic properties and homogeneity remained stable. The pH, viscosity, adhesion, and spreadability tests met the criteria for quality preparations, and irritation tests showed no adverse skin reactions. Analysis of variance (ANOVA), followed by Tukey's post-hoc test, indicated significant differences (p < 0.05) in antibacterial activity among all emulgel formulations. In conclusion, Formula F3 (15% extract) showed the best antibacterial activity and met all physical evaluation parameters, confirming that the jamblang seed emulgel is a high-quality and safe formulation. A paired t-test showed all parameters were statistically significant (p > 0.05).